Toward Improving the Transition of Patients With Congenital Adrenal Hyperplasia From Pediatrics to Adult Healthcare in Japan - Takasawa, Kei; Kashimada, Kenichi (Frontiers in Pediatrics, 2022)
The transition of patients with childhood-onset chronic diseases from pediatric to adult healthcare systems has recently received significant attention. Since 2013, the Japan Pediatric Society developed working groups to formulate guidelines for the transition within their disease specialty. Herein, we report activities of the Japan Society of Pediatric Endocrinology (JSPE) and the current status of transition medicine for 21-hydroxylase deficiency (21-OHD) in Japan. JSPE proposed roadmaps and checklists of transition and prepared surveys on the current status of healthcare transition of childhood-onset endocrine diseases. In Japan, newborn screening for 21-OHD started in January 1989; however, there is no nationwide, registry-based longitudinal cohort study of 21-OHD from birth to adult. The current status and the whole picture of healthcare and health problems in adult patients with 21-OHD remains unclear. Thus, we conducted a questionnaire survey of JSPE members to clarify the current status of healthcare transition in 21-OHD, and discuss future perspectives for the healthcare transition of 21-OHD patients in Japan.